A comparison of the Health Star Rating and nutrient profiles of branded and generic food products in Sydney supermarkets, Australia. Issue 11 (26th March 2019) - Kim, Dong Hun; Liu, Wing Gi Amanda; Rangan, Anna; Gemming, Luke
Abstract: Objective: To compare the Health Star Rating (HSR) and the nutritional profile of branded and generic packaged foods in Australia. Design: In-store audits of packaged food products capturing data on HSR and nutritional content to analyse differences between branded and generic foods across ten food categories. Setting: The audit was conducted in four major supermarket chains across various locations within metropolitan Sydney regions, Australia. Results: A total of 6269 products were analysed with 57 % of generic products and 28 % of branded products displaying an HSR. The median HSR of branded products was significantly greater than for generic products overall (4·0 v . 3·5, P <0·005) and in six out of ten food categories ( P <0·005). However, when branded products could be matched to their generic counterparts for paired comparisons ( n 146), no statistical difference was observed in all ten food categories. Branded products that chose to display an HSR had significantly lower saturated fat and Na, but higher fibre contents than branded products not displaying an HSR. Conclusions: Our data show no difference in the HSR or nutrient profiles of similar branded and generic products that display HSR. Branded products appear to exploit the voluntary nature of the HSR scheme, preferentially displaying an HSR on healthier products compared with their generic counterparts.